MEMBANGUN PEREKONOMIAN MANDIRI MELALUI DESA TEMATIK BERBASIS PENGUATAN TEKNOLOGI HOME INDUSTRY BATIK DI DESA REK KERREK PEMEKASAN - Tampubolon, Liosten Rianna Roosida Ully; Sayidah, Nur; Marwiyah, Siti; Muharrom, Muharrom (Jurnal Abdi Insani, 2024)
The production process of Batik Tulis in Rek Kerrek Village, Pamekasan Regency, uses conventional methods, so there are problems, the capacity, quality, and competitiveness of written batik products are still low. The purpose of the PDB program is to provide technological innovations such as a malam pelorot machine and hand printing so as to minimize product damage and increase production capacity, sales volume, and competitiveness of batik products. The methods used are training, mentoring and practicing technological innovations on partners.  The results of the program achievements: 1) Hand printing machines (partner-1) and malam pelorot machines (partner-2) increase production capacity and quality, sales volume and minimize defective products, 2) Training, mentoring, and practice of making promotional content increase the knowledge and skills of making promotional content for partners, 3) Training, mentoring, and practice of making e-commerce increase partners' knowledge and skills in using e-commerce, 4) Training, mentoring, and practice of marketing mix strategies increase partner sales volume, 5) Training, mentoring and practice of accounting bookkeeping increase partner knowledge and skills in bookkeeping.